Effect of Xuanwei Ham Proteins with Different Ripening Periods on Lipid Metabolism, Oxidative Stress, and Gut Microbiota in Mice. Issue 18 (9th August 2022) - Guo, Jie; Xu, Feiran; Xie, Yong; Chen, Bo; Wang, Ying; Nie, Wen; Zhou, Kai; Zhou, Hui; Xu, Baocai
Abstract : Scope: Consumption of dry‐cured ham may have a cardiovascular disease preventive capacity. However, whether ham protein in the maintenance of health and prevention of disease is dependent on ripening periods need to be clarified. Methods and results: Fifty C57BL/6 mice consume a diet that contains either Casein, raw ham protein (XWH0), or Xuanwei ham protein after 1‐, 2‐, or 3‐years of maturation (XWH1, XWH2, or XWH3) for 4 weeks. Results show that longer ripening periods in the Xuanwei ham groups are negatively correlated with body weight gain, adipose tissue weight, total cholesterol (TC), and triglycerides levels in serum and liver, and these proteins intake could maintain liver health, reduce lipid deposition and oxidative stress, regulate lipid metabolism‐related genes expression, alter the gut microbiota, and promote short‐chain fatty acid production. Remarkably, XWH3 intake maintains lower TC and low‐density lipoprotein cholesterol levels in serum and has high antioxidative activity as well. This regulation of lipid metabolism and oxidative stress may be related to the AMPK/Nrf2 signaling. Conclusion: Xuanwei ham dietary proteins that have endured a specific ripening period may have preventive effects on metabolic syndrome, which provide a basis for new ideas for nutritional health interventions. Abstract : The growth performance, lipid metabolism, oxidative stress, gut microbiota, and metabolites of mice are systematically evaluated by feeding Xuanwei ham protein diets at different ripening periods. In order to further study the molecular mechanism of ham protein at different maturity stages on lipid metabolism and oxidative stress in mice, the AMPK/Nrf2 signaling pathway is detected.